“Musik fra Christian IIIs tid” – nogle supplerende oplysninger til udgivelsen i Dania Sonans IV og V - Glahn, Henrik; Bergsagel, John (Danish Yearbook of Musicology, 1989)
The editor of Music from the Time of Christian III (Dania Sonans IV (1978) and V (1986) offers the following details supplementary to the information contained in the edition. The first concerns the composer Jørgen Preston, who was the leader of the Royal Chapel singers ca. 1545-1553. As his country of origin has always been a matter of uncertainty, it is of interest to learn that in a newly-discovered source in which his having absolved the “magister” degree at Copenhagen University in May 1545 is recorded, he appears under the name Georgius Preston Scotus. His way from Scotland to Denmark, whether direct or indirect, has not yet been investigated. Secondly, the motet Constitues eos a 6 voc. (Dania Sonans V, pt.2,no.1), wrongly attributed to Gombert in one of the part books, also occurs in “The Lublin Tablature”, a Polish source contemporary with the Danish MSS (ca. 1540), in a 5-part version arranged for organ. The model for the organ arrangement is present i D, A, T, V and B of the Danish version. Finally, the studies of M. Ruhnke add to the biography of Erhart Herdegen, who succeeded Jørgen Heyde as leader of the Royal Chapel in 1556 and was evidently responsibie for a second set of part books incompletely preserved in the Royal Library in Copenhagen that E.H. served as trumpeter at the German Ducal Chapel in Würtemberg (Stuttgart) in the years before 1550, when he was appointed a trumpeter by Christian III. The editor is preparing a closer examination of the repertory contained in Herdegen’s part books which will be published at a later date.